Praktik Keagaman Aliran Kejawen Aboge di antara Agama Resmi dan Negara - Ulumuddin, Moch. Ichiyak (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
Aliran Kepercayaan constitutes a cultural heritage of Indonesia, inherited from generation to generation. Aliran Kepercayaan however have been often measured on the perspective of Indonesian six official religions that eventually bear misjudgment. The divergent of belief system either in terms of religious teachings and practices finally comes as counter argument in responding the existence of Aliran Kepercayaan. This article tries to examine the existence of Aliran Kepercayaan in Mojokerto namely Aboge religiously and socially in relation with the social and political condition of Indonesia. State’s constitution indeed guarantees religious freedom for the people to worship in accordance with someone’s belief. However, the reality is different at all. Some Aliran Kepercayaan experienced persecution by religious extremist and by the State. Aboge itself often becomes controversial for its Muslim neighborhood. Negative and positive assumption are attached on them in an exchange. Two different interpretations reflect on the Aboge’s religious practices and teachings. For this reason, this article attempts to scrutinize the religious practices and teachings in correlation with spiritual tradition on the Javanese people that specialized mysticism in any matters. It also is aimed to explain the state intervention toward the religious life of Aliran Kepercayaan based on the perspective of six official religions.